Measurement Method of Static Friction by a Piezoelectric Impact Drive Mechanism - Atsushi Okuno (Japanese Society of Tribologists, 2008)
The coefficient of static friction is one of the basic factors of actuator performance; it influences the operational characteristics of actuators. In this present study we focus on the dependence of the coefficient of static friction on the time of stationary contact through experiments .We start with the development of a static friction measurement device that can control extremely short contact time durations (approximately 5 ms), using an inertia drive system.